2012
DOI: 10.1038/tp.2012.132
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal fatty acid composition in the frontopolar cortex of patients with affective disorders

Abstract: Bipolar and major depressive disorders are essentially relapsing and remitting disorders of affect with nearly full recovery between episodes. Although the underlying molecular mechanisms remain unclear, myelin-related abnormalities have long been suspected. Here, using novel statistical analysis, we show that subtle but significant abnormalities exist in the composition of fatty acids (FAs), including docosapentaenoic acid (22:5n-3), one of the omega-3 polyunsaturated FAs, found in the post-mortem frontopolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…We could not determine whether the results that we observed were due to the effects of psychotropic drugs, although NIRS signals were not correlated with drug dosage. For example, a very recent study reported that carbamazepine extended-release treatment normalized frontopolar activation in manic youths with BD [55], and that postmortem brain tissue from medicated patients with BD exhibited impaired myelination in the frontopolar cortex [56]. Thus, there remains a possibility that the association found in this study was due to the treatment and the long-term course of the disorder.…”
Section: Discussionmentioning
confidence: 84%
“…We could not determine whether the results that we observed were due to the effects of psychotropic drugs, although NIRS signals were not correlated with drug dosage. For example, a very recent study reported that carbamazepine extended-release treatment normalized frontopolar activation in manic youths with BD [55], and that postmortem brain tissue from medicated patients with BD exhibited impaired myelination in the frontopolar cortex [56]. Thus, there remains a possibility that the association found in this study was due to the treatment and the long-term course of the disorder.…”
Section: Discussionmentioning
confidence: 84%
“…Our data shows that the metabolism of sphingolipids and phospholipids is significantly altered by stress in both the PFC and the hippocampus, suggesting SMase, PLA2 and PLD as potential therapeutical targets for stress-related disorders. These alterations in lipid signaling pathways have several implications in physiological mechanisms, such as, neurogenesis and synaptic plasticity, known to be implicated in several stress-related disorders, such as emotional disorders 15, 4951 , and eventually other psychiatric disorders, such as schizophrenia 5154 . Given that there are different SMase, PLA2 and PLD isozymes, future lipidomic studies addressing the impact of lipid signaling-targeted therapeutical drugs will provide the pharmacological mechanistic insights in order to choose the best candidate drug in a given pathological condition.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It remains to be determined whether PUFA-modulated signaling pathways influence the molecular responses in oligodendrocyte lineage cells in response to behavioral experiences, so additional studies are needed to understand if, and how, these "inputs" may converge at the molecular level. However, abnormalities in the composition of PUFAs have been identified in the frontopolar cortex of bipolar and major disorder patients (Tatebayashi et al, 2012). Analysis of PUFA content in erythrocytes and diffusion tensor imaging performed in patients with psychotic disorders established a correlation of decreased PUFAs and fractional anisotropy, a measurement of water movement correlated with white matter integrity (Peters et al, 2013).…”
Section: Common Effectors? the Potential For Intersecting Mechanisms mentioning
confidence: 99%